A review of palm mesocarp maceration and separator machine - Wondi, Mohd Hafizz; Shamsudin, Rosnah; Yunus, Robiah (Malaysian Society of Agricultural Engineers, 2019)
The most usual method of extraction crude palm oil is by pressing mescarp fiber and nut together using screw press. Due to this reason, nut and kernel are tend to break by exerted pressing pressure from screw press thus resulting in high kernel loss. Over the years there are many tools and machine have been developed for fiber and nut separation. There are several technique have been introduced to separate mesocarp from its nut including manual or power operated machine. Manual tools are depend on the skill of the worker itself thus, operated machine are developed to eliminate the limitation of manual tools. Most recent separation machine design and technology being discuss in this work has been conferred for various objectives and not only limited for fiber and nut separation before oil extraction. This review paper aims to bring a further understanding on the design, capabilities and limitation from different technique of fiber and nut separation have been used specifically for palm oil industries.